(untitled) (Gestão & Regionalidade, 2025)
In Brazil, the financial services authority are the Ministry of Economy and the CVM (Securities and Exchange Commission), and they regulate the quality of information provided by companies and the activity of audit committee to ensure the interest of investors. If the requirements are not accordingly, the financial statements are requested to be redone. With the purpose to identify the main causes that led the CVM request the redoing of the financial statements of 25 companies, this study tries to understand the motivation behind these determination by analyzing the republications of annual and quarterly statements inspected in the period from 2009 to 2021. The research considered 49 determining standards for organizations to represent quarterly and annual financial statements. Therefore, the established standards foreseen that they must be rectified to make them relevant and reliable, in the correct classification of financial instruments and the measurement of investments are the main points to be corrected and/or added.